Advances and Challenges in Cervical Cancer: From Molecular Mechanisms and Global Epidemiology to Innovative Therapies and Prevention Strategies - Raiyan Ul Hakim BSc; Tasbir Amin BSc; S M Bakhtiar Ul Islam PhD (Cancer Control)
Background In the global scenario of public health, cervical cancer poses a major threat with high mortality rates, especially in women. New incidence cases and prevalence vary across different regions, as recently shown by GLOBOCAN data. The development of cervical cancer is primarily due to persistent infection by high-risk genotypes of human papillomavirus (HPV), which is a multifaceted process that is influenced by genetic, environmental, and lifestyle factors. Purpose The goal of this study is to thoroughly investigate cervical cancer, including its etiology, molecular mechanisms, progression, diagnosis strategies, and current therapies. This review further highlights the transformative power of HPV vaccination and screening programs in curbing the disease’s burden and potentially promising novel approaches like immunotherapy and targeted therapy. Research Design This is a narrative review article that summarizes previous literatures regarding cervical cancer in terms of molecular mechanism, etiology, clinical developments, and prevention. Study Sample The review encompassed studies from diverse sources, including experimental, observational, and clinical research published between 1992 and 2025. Data Collection and/or Analysis Data were collected through comprehensive literature searches using databases such as PubMed, Scopus, and the Cochrane Library with defined inclusion and exclusion criteria. Results Nonetheless, there are gaps in research and controversies regarding vaccine coverage, screening practices, and treatment accessibility for poor populations. Precision medicine trends are emerging along with new biomarkers for early detection and personalized treatment, which also form part of this discussion. Key findings include the critical role of prevention measures in controlling the global impact of cervical cancer. Conclusions The paper synthesizes the existing knowledge and identifies gaps that require further research, which is significant in augmenting prevention, diagnosis, and treatment of cervical cancer towards addressing its public health implications worldwide.